An advanced high energy-efficiency rechargeable aluminum-selenium battery. (December 2019) - Liu, Shiqi; Zhang, Xu; He, Shiman; Tang, Yushu; Wang, Jie; Wang, Boya; Zhao, Shu; Su, Heng; Ren, Yang; Zhang, Liqiang; Huang, Jianyu; Yu, Haijun; et al.
Abstract: Aluminum-ion batteries (AIBs) are considered as a promising alternative to traditional rechargeable batteries due to their high theoretical capacity, low cost, and multivalent-ion/multi-electron transfer, but are hindered from commercialization by the lack of suitable cathode materials. Herein, an aluminum-selenium (Al-Se) battery that operates at room temperature with high energy efficiency is reported. This Al-Se battery exhibits high selenium utilization with a discharge capacity of 607 mAh g −1, a reduced overpotential, and high volumetric capacity for over 100 cycles. Furthermore, ex-situ spectroscopic and microscopic investigations of the Se cathodes indicated the existence of an aluminum selenide component as the discharge product. Additionally, in-situ transmission electron microscopy provided not only insights into understanding the Al-Se electrochemistry, but also a real-time characterization technique to evaluate the electrochemistry of AIBs in general. Graphical abstract: An advanced rechargeable aluminum-selenium battery, which possesses a high energy-efficiency, a large active material utilization, a reduced overpotential and a valuable long-cycle performance, was developed. Ex-situ and in-situ spectroscopic and microscopic measurements were performed in this system shedding lights on the proof of the underlying reaction mechanisms in aluminum-based batteries. Image 1 Highlights: A new aluminum-selenium (Al-Se) battery is demonstrated. The results show a high energy-efficiency Se cathode in aluminum-ion batteries. The reaction mechanism of multielectron/multivalent-ion transfer is proposed. The reaction mechanism was first confirmed by in-situ TEM tests.